(untitled) (Research, Society and Development, 2020)
It is a cross-sectional study, typified by a quantitative approach, whose main objective is to evaluate the impact of the national health campaign “Noviazgo sin violencia”, promoted by Ministerio de la Mujer del Paraguay, among members of the academic community of Federal University of Latin American Integration, in 2018. A semi-structured questionnaire was applied to 108 individuals, with greater female participation (56.6%), registering a lower age limit of 17 years and a higher age of 59 years. It was observed that 30.55% of the participants rated the information provided by the campaign as "good"; 28.7% considered them "important" and 17.6% said they were "interesting". On the other hand, 90.7% of the participants determined that the content of the campaign is of high public utility. The data showed that only 62% said they knew of any institution to report this type of violence. Regarding the target audience of the campaign, 50.93% said it was aimed at both men and women. This work highlights the importance of conducting this type of research not only within the university, but also in other social construction environments, seeking to understand complex realities through a multilateral vision, in the individual and collective sphere of violence as a matter Public/Collective Health.